Diamond, Diamond-Like Carbon (DLC) and Diamond-Like Nanocomposite (DLN) Thin Films for MEMS Applications - Santra, T. S.; Bhattacharyya, T. K.; Patel, P.; Tseng, F. G.; Barik, T. K. (IntechOpen, 2012)
None